Preparation method of cottonrose hibiscus leaf flavone and polysaccharide, hydrogel prepared from cottonrose hibiscus leaf flavone and polysaccharide and application of hydrogel
By preparing hydrogel dressings for flavonoids and polysaccharides of hibiscus, the problem of diabetic ulcer treatment is solved, efficient drug delivery and precise efficacy are achieved, and better clinical treatment options are provided.
Patent Information
- Application Number
- CN202510363032.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-05-09
AI Technical Summary
Diabetic ulcers (DU) are difficult to treat, traditional drug administration methods are inconvenient and the efficacy is uncertain, and the prior art is difficult to effectively solve this public health problem.
A method of preparing flavonoids and polysaccharides of hibiscus is used to obtain hibiscus flavonoid extract by ultrasonic extraction and separation and purification of macroporous resin. Combining sodium alginate and hibiscus leaf polysaccharides, the hibiscus leaf hydrogel was prepared as a dressing by cross-linking reaction.
The hibiscus leaf hydrogel significantly improves the drug delivery efficiency and has a precise therapeutic effect on diabetic ulcers. It has a simple and easy preparation method and low cost, providing better drug and dosage form choices for the clinical treatment of diabetic ulcers.
Smart Images

Figure CN119950568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Chinese medicine extracts and preparations, and in particular to a method for preparing hibiscus leaf flavonoids and polysaccharides, a hydrogel prepared therefrom and applications thereof. Background Art
[0002] Diabetic ulcers (DU) are one of the common chronic complications in diabetic patients, which not only leads to high disability and mortality rates, but also has a long and expensive treatment process. In addition, there are certain limitations in the choice of treatment methods, which makes it a public health problem that needs to be solved urgently.
[0003] Hibiscus mutabilis L., also known as hibiscus leaf, is the leaf of Hibiscus mutabilis L., a plant of the Malvaceae family. Hibiscus mutabilis L. has been a good medicine for treating carbuncle and malignant ulcer since ancient times. In the traditional Chinese medical system, DU belongs to the category of "carbuncle". There is no report on the use of Hibiscus mutabilis L. for DU. The use of Hibiscus mutabilis L. for the treatment of common carbuncle and malignant ulcer has problems such as inconvenience of traditional administration and uncertain efficacy. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a flavonoid extract from Hibiscus mutabilis leaves to solve the above problems.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a method for preparing a flavonoid extract from hibiscus leaves, comprising the following steps:
[0006] (1) After the dried Hibiscus mutabilis leaves are crushed, ethanol with a volume percentage concentration of 60% to 90% is added, and the solid-liquid ratio is 1:10 g / ml to 1:40 g / ml, and ultrasonic extraction is performed to obtain a Hibiscus mutabilis leaf extract;
[0007] (2) The hibiscus mutabilis leaf extract obtained in step (1) is separated and purified using a macroporous resin to obtain a hibiscus mutabilis leaf flavonoid extract.
[0008] Preferably, in step (1), ultrasonic extraction is performed twice, each time for 10 min to 30 min; the volume percentage concentration of the ethanol is 60% to 80%; and the solid-liquid ratio is 1:10 g / mL to 1:30 g / mL.
[0009] Further preferably, the ultrasonic extraction is performed for 26 min each time, the volume percentage concentration of ethanol is 66%, and the solid-liquid ratio is 1:26 g / mL.
[0010] Preferably, in step (2), AB-8 macroporous resin is used as the adsorption resin, the concentration of the loading solution is 1 to 3 g / mL, the loading flow rate is 1 to 3 mL / min, and the eluent is ethanol with a volume percentage concentration of 30% to 60%.
[0011] The inventors of this application used network pharmacology and molecular docking technology to predict the active ingredients of Hibiscus mutabilis leaves for treating DU. The results showed that rutin, luteolin, hyperoside, etc. may be the main active ingredients; these active ingredients act on key targets such as EGFR, TNF, AKT1, MMP9, and then play a role in treating DU by participating in Wnt / β-catenin, PI3K-Akt signaling pathways, JAK-STAT signaling pathways, etc. Therefore, the inventors used these active ingredients as the criteria for effective extraction and studied the appropriate extraction and separation methods, thus laying the foundation for the hibiscus leaf flavonoid extract as the active ingredient of the hydrogel preparation for treating DU.
[0012] The second object of the present invention is to provide a method for preparing a polysaccharide extract from Hibiscus mutabilis leaves, comprising the following steps:
[0013] (1) Pretreatment: The Hibiscus mutabilis leaf powder was pretreated to remove pigments;
[0014] (2) Extraction: The polysaccharide from Hibiscus mutabilis leaf was extracted by papain extraction method;
[0015] (3) Purification: First, the TCA method is used to remove the protein, and then cellulose column chromatography is used to obtain Hibiscus mutabilis leaf polysaccharide.
[0016] Preferably, in step (1), the pretreatment method is: Soxhlet extraction with 95 vol% ethanol for 2 h;
[0017] In step (2), the enzyme concentration was 1.23%, the enzymatic hydrolysis time was 2.45 h, the enzymatic hydrolysis temperature was 50°C, and the solid-liquid ratio was 1:58 g / mL;
[0018] In step (3), the concentration of trichloroacetic acid added during deproteinization is 5 wt %, and after adjusting the pH to neutral, heating is performed at 60° C. for 30 min. A DEAE-52 cellulose column is used for column chromatography, and a NaCl solution is used for gradient elution.
[0019] The leaves of Hibiscus mutabilis are slippery and sticky. The inventors have found that the mucus is a polysaccharide component. The inventors have extracted and purified the polysaccharide component in order to use it as a component of hydrogel dressings.
[0020] The third purpose of the present invention is to provide a hibiscus leaf hydrogel, the technical scheme adopted is that the hibiscus leaf hydrogel is a composite of two materials, hibiscus leaf polysaccharide and sodium alginate prepared by the aforementioned method, as a matrix material, loaded with hibiscus leaf flavonoids prepared by the aforementioned method as an effective ingredient, and is obtained by cross-linking with a cross-linking agent.
[0021] The inventors of this application have proved through a large number of experiments that Hibiscus mutabilis leaf polysaccharide has gel-forming ability, can be used as a dressing for wound healing, and can also be used as a carrier for drug delivery. It is also proved that the organic combination of Hibiscus mutabilis leaf polysaccharide and sodium alginate can not only improve the physical and chemical properties of the hydrogel, but also improve the therapeutic effect of diabetic ulcers, playing the role of "drug-adjuvant combination".
[0022] Preferably, the specific preparation method is: 2wt% to 6wt% of sodium alginate (SA), 2wt% to 6wt% of hibiscus leaf polysaccharide, and 2wt% to 6wt% of hibiscus leaf flavonoids are mixed in a volume ratio of (1-2):(1-4):(1-2), poured into a mold, and sprayed with a cross-linking agent CaCl2 with a concentration of 1wt% to 2.5wt% to obtain hibiscus leaf hydrogel.
[0023] Further preferably, the specific preparation method is: 4wt% of sodium alginate, 2wt% of hibiscus leaf polysaccharide and 4wt% of hibiscus leaf flavonoids are mixed in a volume ratio of 1:1:1, poured into a mold, and sprayed with a cross-linking agent CaCl2 with a concentration of 2wt% to obtain hibiscus leaf hydrogel.
[0024] A fourth object of the present invention is to provide a use of the above-mentioned hydrogel in the preparation of a medicament for treating diabetic ulcers.
[0025] Compared with the prior art, the advantages of the present invention are: the hibiscus leaf hydrogel dressing of the present invention can significantly improve the drug delivery efficiency, has a definite therapeutic effect on diabetic ulcers, and the preparation method is simple and easy with low cost, providing better drug and dosage form options for the clinical treatment of diabetic ulcers. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 HPLC chromatograms of the reference substance (A) and the aqueous solution of hibiscus leaf flavonoids (B);
[0027] Figure 1 Among them, 1. rutin; 2. hyperoside; 3. luteolin;
[0028] Figure 2 The results of extraction and determination are shown in different ethanol concentrations;
[0029] Figure 3 The effect of different Hibiscus mutabilis leaf polysaccharide concentrations on the microstructure of hydrogels;
[0030] Figure 4 The wound conditions of rats at 0, 3, 7, and 14 days. DETAILED DESCRIPTION
[0031] The present invention will be further described below with reference to the examples. It should be noted that, in the following examples and comparative examples, the percentages of ethanol, unless otherwise specified, are all percentages by volume.
[0032] Embodiment 1:
[0033] As a preferred embodiment, a method for extracting, separating and purifying flavonoids from Hibiscus mutabilis leaves comprises the following steps:
[0034] (1) Pretreatment: Wash the fresh leaves of Hibiscus mutabilis, dry them in an electric hot air drying oven at 60°C, grind them and pass them through a 50-mesh sieve, and the sieved material is the Hibiscus mutabilis leaf powder;
[0035] (2) Extraction: Weigh 5.0 g of Hibiscus mutabilis leaf powder and use 66% ethanol for ultrasonic extraction twice, with each extraction time of 26 min and a solid-liquid ratio of 1:25 g / mL to obtain an extract;
[0036] (3) Separation and purification: The extract obtained in step (2) was concentrated, and after the temperature dropped to room temperature, it was refrigerated at 4°C for 24 h, filtered, and the residue was discarded. This was used as the sample solution for the purification process. The sample solution concentration was 2.43 mg / mL.
[0037] After conventional pretreatment, 20.00 g of the macroporous resin AB-8 was weighed and loaded into the chromatography column. Then 30 mL of the above-mentioned sample solution was transferred and washed with distilled water until the effluent was colorless and transparent. The elution operation was carried out using 60% ethanol at a flow rate of 1.8 mL / min, and the volume of the eluent was 70 mL. Three groups of parallel verification experiments were carried out according to the above-mentioned optimal elution conditions. The results showed that the average purity of the crude extract of total flavonoids was 16.76%; the average purity of the purified flavonoids was 53.68%.
[0038] Subsequent Examples 3 and 4 are Hibiscus mutabilis leaf polysaccharides prepared by the above method.
[0039] The process of exploring the optimal process of this embodiment is as follows:
[0040] 1. Establishment of the determination method of flavonoids content in Hibiscus mutabilis leaves:
[0041] 1.1 Chromatographic conditions: A RD-C18 column (specifications: 4.6 mm × 250 nm, 5 μm) from Zhongpu Technology was used, with 0.3 wt% phosphoric acid aqueous solution (phase A)-tetrahydrofuran (phase B) as the mobile phase, and separation was performed by gradient elution. The specific elution program is shown in Table 1. The column temperature of the chromatographic analysis was set at 30 °C, the detection wavelength of the UV detector was 359 nm, the flow rate was controlled at 1.0 mL / min, and the injection volume was fixed at 20 μL;
[0042] Table 1 Gradient elution program for HPLC detection of flavonoids from Hibiscus mutabilis leaves
[0043]
[0044] 1.2 Preparation of reference solution:
[0045] Weigh appropriate amounts of three flavonoid component reference substances, dissolve them in methanol as a solvent, and finally dilute to a total volume of 10 mL to prepare a mixed reference substance solution containing 0.100 mg of rutin, 0.026 mg of hyperoside, and 0.013 mg of luteolin per 1 mL;
[0046] 1.3 Preparation of test solution: Extract according to the extraction method of step (2) of Example 1, then filter and collect the filtrate, concentrate it by rotary evaporation at 65°C and 80 r / min, make up to 50 mL volumetric flask with anhydrous ethanol, and filter through a 0.22 µm microporous membrane to obtain the solution;
[0047] 1.4 Carry out sample analysis according to the chromatographic conditions in 1.1. The chromatograms of the reference and test samples are shown in Figure 1 The results showed that the retention times of rutin, hyperoside and luteolin in flavonoids were consistent with those of the reference solution, and the separation degrees were all greater than 1.5, indicating that the chromatographic conditions could effectively separate the target components.
[0048] 1.5 Linear relationship investigation: Accurately measure the mixed reference solution in 1.2 and dilute it with methanol into five different concentration gradients, as shown in Table 2; measure according to the chromatographic conditions in 1.1, with the concentration of each solution as the X-axis and the corresponding peak area as the Y-axis, and draw a standard curve; Results:
[0049] Rutin: Standard curve: y=5×10 7 x+8994, correlation coefficient r: 0.9997, linear range (μg / mL): 6.250~100.000;
[0050] Hyperoside: Standard curve: y=5×10 7 x-15713, correlation coefficient r: 0.9993, linear range (μg / mL): 1.650~26.400;
[0051] Luteolin: Standard curve: y=9×10 7 x-18622, correlation coefficient r: 0.9995, linear range (μg / mL): 0.800~12.800.
[0052] Table 2 Concentration of reference substances
[0053]
[0054] 1.6 Precision investigation: Accurately measure the medium-concentration mixed reference solution under Item 1.4, and perform the determination according to the chromatographic conditions under Item 1.1. Inject the sample six times continuously, and investigate the instrument precision of HPLC by detecting the changes in the peak areas of rutin, hyperoside, and luteolin.
[0055] Results: The peak area of rutin was 1234421.5, RSD: 0.40%; the peak area of hyperoside was 344198.5, RSD: 0.21%; the peak area of luteolin was 286144.67, RSD: 0.30%.
[0056] 1.7 Stability study: Prepare the test solution according to the method in 1.3, and measure according to the chromatographic conditions in 1.1. Inject 20 μL at 0, 2, 4, 8, 12, and 24 h, and record the peak area at each time point to study the stability of rutin, hyperoside, and luteolin within 24 h. The RSD is shown in Table 3. The results show that the test solution has good stability within 24 h.
[0057] Table 3 Stability test results
[0058]
[0059] 1.8 Repeatability study: Prepare 6 test sample solutions in parallel according to the method in 1.3, and measure according to the chromatographic conditions in 1.1. Record the peak areas of rutin, hyperoside, and luteolin and calculate the contents to examine the repeatability of the method. The contents of rutin, hyperoside, and luteolin and their RSDs are shown in Table 4. The results show that the method has good repeatability.
[0060] Table 4 Repeatability test results
[0061]
[0062] 1.9 Recovery rate investigation: Accurately weigh about 2.50 g of dried powder of Hibiscus mutabilis leaves, add rutin, hyperoside, and luteolin reference solution with the same content as the medicinal material, evaporate the solvent, and prepare 6 test solution in parallel according to the method under 1.3. Determine according to the chromatographic conditions in 1.1, and calculate the sample recovery and relative standard deviation (RSD) of rutin, hyperoside, and luteolin;
[0063] Results: The average recoveries of rutin, hyperoside, and luteolin were 99.65%, 98.68%, and 99.25%, respectively, and the RSDs were 1.04%, 2.16%, and 2.12%, respectively. The data showed that this method had a high accuracy in determining the above three flavonoid active ingredients.
[0064] 2. Exploration of extraction conditions
[0065] 2.1 Screening of extraction times
[0066] The test solution was prepared according to the method described in 1.3, extracted 1 time, 2 times, and 3 times, and tested according to the chromatographic conditions of 1.1. The peak area was recorded, and the content of each active ingredient was calculated based on it, and the effect of different extraction times on the content of each active ingredient in flavonoids was studied. The results showed that with the increase of the number of extractions, the peak areas of rutin, hyperoside, and luteolin all showed an upward trend; considering the time cost, the number of extractions was set to 2 times.
[0067] 2.2 Screening of extraction time
[0068] The test solution was prepared according to the method in item 1.3, and the extraction time was 10, 20, 30, and 40 min. The test was carried out according to the chromatographic conditions in item 1.1. The peak area values of each group were recorded, and the content of each effective component was calculated based on this, and the effect of different extraction times on the content of each effective component in flavonoids was studied. The results showed that the content of rutin and hyperoside reached the maximum at 30 min, and there was no obvious upward trend afterwards, and hyperoside increased slightly from 10 to 30 min. Considering the extraction effects of the three substances, it is more appropriate to select an extraction time range of 10 to 30 minutes. The contents of the three components in this range can be maintained at a high level.
[0069] 2.3 Screening of ethanol concentration
[0070] The test solution was prepared according to the method described in 1.3, with ethanol concentrations of 60%, 70%, 80%, and 90%, respectively, and the detection was carried out according to the chromatographic conditions of 1.1. The peak area obtained was recorded, and the content of each active ingredient was calculated based on it, and the effect of different ethanol concentrations on the content of each active ingredient in flavonoids was studied. The results are shown in Figure 2 . The study found that rutin and hyperoside reached the maximum extraction amount at 70% ethanol concentration, while luteolin showed the maximum peak area at 80% ethanol concentration. In addition, it was observed that the extraction efficiency of luteolin decreased significantly when the ethanol concentration was below a certain threshold. When the ethanol concentration exceeded a certain limit, the extraction efficiency of rutin and hyperoside also decreased. In view of this, in order to achieve the maximum extraction rate of the three flavonoid components, after comprehensive consideration, it is believed that the ethanol concentration range of 60% to 80% is appropriate.
[0071] 2.4 Screening of material-liquid ratio
[0072] The sample solution to be tested was prepared according to the method described in 1.3, with the solid-liquid ratio of 1:10, 1:20, 1:30, and 1:40 g / mL, respectively, and the detection was carried out according to the chromatographic conditions of 1.1. The peak area obtained was recorded, and the content of each active ingredient was calculated based on this, and the effect of different extraction times on the content of each active ingredient in flavonoids was studied. The results showed that the peak area of rutin was the largest when the solid-liquid ratio was 1:10 g / mL, and the peak areas of hyperoside and luteolin were the largest when the solid-liquid ratio was 1:10-1:20 g / mL, so it was more appropriate to select a solid-liquid ratio in the range of 1:10-1:30 g / mL.
[0073] 2.5 Box-Behnken response surface design
[0074] The inventors took the results of the single-factor experiment as the starting point, adopted the central composite design of the response surface method, set the extraction time (A), ethanol concentration (B) and solid-liquid ratio (C) as independent variables, and fixed the number of extractions to two times. The response value selected the AHP-CRITIC mixed weighted comprehensive score of the content of three flavonoid active ingredients. On this basis, a three-factor three-level experimental scheme was designed. The specific experimental design details can be found in Table 5. With the help of Design-Expert 12 software, the Box-Behnken design principle was adopted, and 17 groups of experimental schemes were finally generated. According to the 17 sets of precise parameters provided by the software, the test solution was prepared and measured according to the high-performance liquid chromatography conditions described under 1.1.
[0075] Table 5 Factor level table
[0076]
[0077] 2.6 Establishment of flavonoid evaluation index weights
[0078] 2.6.1AHP method
[0079] AHP is the analytic hierarchy process. Based on the pharmacological effect intensity of different active ingredients, the overlap of network pharmacology targets and the compatibility rules, this study used the contents of three active ingredients in flavonoids as weight indicators for quantitative analysis and constructed a hierarchical weight system. By establishing a pairwise comparison priority judgment matrix, each indicator was given a relative score, and the weight coefficient and consistency ratio factor (CI) of rutin, hyperoside and luteolin were calculated by the sum-product method, and the final results were analyzed. The weight hierarchy of the three target active ingredients in flavonoids was set as: rutin > hyperoside > luteolin. The weight coefficients of rutin, hyperoside and luteolin calculated by the AHP method were 0.5034, 0.2650 and 0.2317, respectively, and the consistency ratio factor (CI) = 0, indicating that the results are consistent and the weight coefficients are valid.
[0080] 2.6.2 CRITIC method
[0081] For the response surface experimental results in Table 6, the inventors first performed a standardized transformation: evaluation index value = (actual observed value - minimum value) / (maximum value - minimum value), and then used SPSSAU software to generate a rank correlation coefficient matrix, and calculated the weight coefficients (ω) of the three flavonoid active ingredients. The weight coefficients of rutin, hyperoside, and luteolin were calculated to be 0.6514, 0.1987, and 0.1498, respectively.
[0082] Table 6 Response surface test results
[0083]
[0084] 2.6.3 AHP-CRITIC mixed weighting method
[0085] The relevant weights of rutin, hyperoside and luteolin were calculated by AHP and CRITIC respectively, and the comprehensive weight was calculated according to formula 1-1.
[0086] (1-1)
[0087] The calculated comprehensive weights of the three flavonoid components were 0.7890, 0.1260, and 0.0835, respectively. AHP, CRITIC, and AHP-CRITIC comprehensive weighting methods were used for comprehensive scoring, and pairwise correlation analysis was performed. The results showed that the correlation coefficients were all 1, indicating that there was a significant correlation between the three (P<0.01). This result verified the consistency of the comprehensive score. Finally, the AHP-CRITIC comprehensive weighting method was selected as the final evaluation method.
[0088] 2.7 Data Analysis
[0089] According to the comprehensive scoring results obtained by the AHP-CRITIC mixed weighted method, response surface optimization was used. Design-Expert 12 software was used to perform multiple linear regression and binomial fitting analysis on three key variables: extraction time (A), ethanol concentration (B), and solid-liquid ratio (C). The regression equation was: Y=351.74-104.98A+46.14B+22.08C-9.68AB+1AC+59.57BC-148.28A 2 -69.13B 2 -50.09C 2. The constructed regression model was subjected to variance analysis to evaluate whether it was statistically significant. In addition, the present application also drew a three-dimensional response surface diagram of the interaction between the factors, and carried out corresponding process verification experiments based on the optimal process parameter combination provided by the software. The P value of the constructed regression model was 0.0006, which was less than the significance level of 0.05, indicating that the model was statistically significant. The P value of the lack-of-fit term was 0.3536, which was higher than the threshold of 0.05. The lack-of-fit test results showed that the model did not respond significantly to the unknown factors, so it can be inferred that the unknown factors had little effect on the model. Based on this, the model has a high degree of credibility in predicting and analyzing the flavonoid extraction process and its comprehensive score. By comparing the F values within the range of each factor, the relative intensity of the influence of the three main factors on the model can be determined, from strong to weak, they are extraction time (B), ethanol concentration (A) and solid-liquid ratio (C).
[0090] By using Design-Expert 12 software to draw a three-dimensional response surface diagram, based on the model fitting results, the optimized optimal process parameters for flavonoid extraction as in Example 1 were determined. Step (2) of Example 1 was carried out in three groups of parallel verification experiments; the results showed that the average content of rutin was 568 μg / g, and the relative standard deviation (RSD) was 0.97%; the average content of hyperoside was 375.49 μg / g, and the RSD was 1.81%; the average content of luteolin was 31.86 μg / g, and the RSD was 1.56%. The average comprehensive score of the process verification reached 393.05, which was close to the predicted value of 391.71, indicating that the extraction process conditions had good stability and feasibility.
[0091] 3. Exploration of separation and purification process
[0092] 3.1 Drawing of standard curve
[0093] Accurately weigh an appropriate amount of rutin standard, dissolve it in methanol and dilute it to an appropriate concentration, and then further dilute it with pure water until each 1 mL of solution contains 1 mg of rutin standard solution. Then take 0.5 mL, 1.0 mL, 1.5 mL, 2.0 mL, and 2.5 mL of the above standard solution and transfer them to a 25 mL volumetric flask, and fill it up to a total volume of 5 mL with water. Add 5 mL of 0.6% sodium nitrite solution to each volumetric flask, stir it thoroughly and let it stand for 6 minutes, then add 0.6 mL of 10% aluminum nitrate solution, mix it again and wait for 6 minutes, then add 3 mL of 4% sodium hydroxide solution, and finally use 70% ethanol to fill it to the mark, shake it well and let it stand for 15 minutes. Using the corresponding reagent as a control, measure the absorbance value of flavonoids at a wavelength of 510 nm, and draw a standard curve based on this. As a result, the standard curve was y = 9.787x + 0.0315, the correlation coefficient r was 0.9995, the concentration range was 0.02~0.1 mg / mL, and the linear relationship was good.
[0094] 3.2 Resin type screening
[0095] 5 g of pretreated polyamide resin, HPD300, DM301, ADS-7, AB-8, and D101 resin were placed in 50 mL conical flasks, 20 mL of sample solution was added, and an oscillation adsorption experiment was performed at 25 °C for 24 h. After the adsorption was completed, the adsorbed resin was washed with distilled water, and then 20 mL of 60% ethanol solution was added. The oscillation was continued for 24 h at the same temperature to achieve effective desorption of flavonoid components. Finally, the content of flavonoids in the desorbed solution was determined. The adsorption efficiency and desorption efficiency of each resin sample were calculated according to formulas (1-2) to (1-4).
[0096] (1-2)
[0097] (1-3)
[0098] (1-4)
[0099] Note: D is the desorption rate, %; C1 is the hibiscus leaf flavonoids after adsorption, mg / mL; %V is the volume of the solution, mL; C2 is the concentration of hibiscus leaf flavonoids in the desorption solution, mg / mL; C0 is the initial concentration of hibiscus leaf flavonoids before adsorption, mg / mL; Q is the adsorption rate; W is the resin mass, g. The results show that although the HPD101 macroporous resin has a high desorption rate, its adsorption rate is relatively low. The adsorption rate of polyamide resin is generally low. Considering the two key indicators of adsorption rate and desorption rate, AB-8 macroporous resin shows a relatively balanced performance, with a high adsorption rate and a moderate desorption rate, so AB-8 macroporous resin is selected as the adsorption resin.
[0100] 3.2 Static adsorption test
[0101] Accurately weigh 5.00 g of AB-8 macroporous resin, place it in a 50 mL conical flask, and add 20 mL of the sample solution to be tested. The adsorption experiment was carried out by oscillator at 25°C for 24 h. During this period, the concentration of flavonoids in the solution was detected regularly until the adsorption rate reached equilibrium. Based on the obtained data, a static adsorption isotherm was drawn. The results showed that within 1 h, about 55% of the flavonoids could be adsorbed on the AB-8 macroporous resin. It fully proves that the AB-8 macroporous resin has good adsorption performance for flavonoids in Hibiscus mutabilis leaves.
[0102] 3.3 Investigation of sample solution concentration
[0103] Weigh 5 portions of pretreated macroporous resin AB-8 accurately, each portion is about 10.00 g, and load them into the chromatography column in sequence. Measure 5 portions of loading solution accurately, each portion has a volume of 100 mL, of which four portions are gradient diluted, and one portion is concentrated to 50 mL before loading. Pass the sample through the chromatography column at a flow rate of 3 s / drop, and collect the column liquid and make it up to 100 mL in a volumetric flask. Determine its absorbance according to the method described in 3.1. The total flavonoid concentration is the horizontal axis, and the adsorption amount and adsorption rate are the vertical axis. The results show that when the loading solution concentration is about 2.43 mg / mL, the adsorption amount and adsorption rate of flavonoids reach a high level. When the loading solution concentration is too high, the adsorption amount and adsorption rate of flavonoids on the AB-8 macroporous resin decrease due to the increase in solution viscosity and resistance; when the loading solution concentration is too low, although the adsorption rate is high, the absolute adsorption amount of flavonoids is relatively low due to the low initial concentration. Taking the adsorption amount and adsorption rate into consideration, a loading concentration of 2.43 mg / mL was selected.
[0104] 3.4 Leakage curve test
[0105] Weigh 20.00 g of the treated macroporous resin AB-8 and load it into the chromatography column. Then transfer 250 mL of the sample solution to the column and pass it through the column at a flow rate of 3 s / drop. Discard the first 10 mL and detect the absorbance of total flavonoids in each fraction (1 10 mL centrifuge tube is 1 fraction). Plot the graph with the tube number as the abscissa and the total flavonoid concentration as the ordinate. The 10% sample solution concentration is the leakage point. The results show that when the sample solution volume reaches 30 mL, the leakage concentration reaches 0.25 mg / mL, which is about 10% of the initial concentration of the sample solution. Therefore, 30 mL is selected as the volume of the flavonoid sample solution. This volume can ensure that the AB-8 macroporous resin is close to saturation during the adsorption process, while avoiding excessive leakage of flavonoids, thereby achieving efficient separation and purification.
[0106] 3.5 Effect of flow rate on adsorption
[0107] 20.00 g of the treated macroporous resin AB-8 was weighed and loaded into the chromatography column. Then 30 mL of the sample solution was transferred and adsorbed at the sample flow rates of 1, 1.4, 1.8, 3.0, and 5.0 mL / min, respectively. The effluent from each tube was collected and the absorbance of flavonoids in the effluent was determined. The flow rate was used as the abscissa, and the adsorption amount and adsorption rate were used as the ordinate to plot the graph. The results showed that when the flow rate was too high, the flavonoids leaked before they were fully adsorbed on the AB-8 macroporous resin, resulting in a significant decrease in the adsorption efficiency; and when the flow rate was too low, although the adsorption efficiency was high, the processing time was significantly extended, increasing the time cost. Therefore, considering the adsorption efficiency and time cost comprehensively, the flow rate was controlled at 1.8 mL / min to achieve the best balance of the adsorption process.
[0108] 3.6 Effect of eluent concentration on adsorption
[0109] Weigh 20.00 g of macroporous resin AB-8 and load it into the chromatography column. Take 30 mL of the sample solution, wash it with distilled water until the effluent is colorless and transparent, then elute it with ethanol concentrations of 30%, 40%, 50%, 60%, and 70% at a flow rate of 1.5 mL / min. Collect the effluent in sections and measure the absorbance of flavonoids. Draw a graph with the concentration of the eluent as the horizontal axis and the desorption rate as the vertical axis. The results show that 60% ethanol has the best desorption effect, reaching 89.33%, and the desorption rate of 30% ethanol is only 16.80%. It can be seen that the total flavonoids are mainly concentrated in the 60% ethanol elution part.
[0110] 3.7 Effect of eluent volume on adsorption
[0111] Weigh 20.00 g of the treated macroporous resin AB-8 and load it into the chromatography column. Then transfer 30 mL of the sample solution, wash it with distilled water until the effluent is colorless and transparent, and use 60% ethanol at a flow rate of 1.5 mL / min for elution. Collect the effluent and measure the absorbance of flavonoids. Draw a graph with the volume of the eluent as the horizontal axis and the desorption rate as the vertical axis. Results When the volume of the eluent reached 70 mL, the elution of flavonoids was basically completed, and the desorption rate reached 94%.
[0112] 3.8 Repeat the verification test
[0113] The best elution method was as follows: the loading solution concentration was 2.43 mg / mL, the loading volume was 30 mL, the flow rate was 1.8 mL / min, the eluent concentration was 60%, and the eluent volume was 70 mL. Three groups of parallel verification experiments were carried out according to the optimal elution conditions. The results showed that the average purity of the crude extract of total flavonoids was 16.76%; the average purity of the flavonoids after purification was 53.68%.
[0114] Embodiment 2:
[0115] As a preferred embodiment, a method for extracting, separating and purifying Hibiscus mutabilis leaf polysaccharides comprises the following steps:
[0116] (1) Pretreatment: Weigh the Hibiscus mutabilis leaf powder and extract it with 95 vol% ethanol for 2 h to remove a large amount of pigments;
[0117] (2) Extraction: The polysaccharides from Hibiscus mutabilis leaves were extracted by papain extraction method with an enzyme concentration of 1.23%, enzymatic hydrolysis time of 2.45 h, enzymatic hydrolysis temperature of 50 °C, and a solid-liquid ratio of 1:58 g / mL.
[0118] (3) Purification: First, deproteinize by TCA method, then use cellulose column chromatography to obtain Hibiscus mutabilis leaf polysaccharide; wherein, the concentration of trichloroacetic acid added during deproteinization is 5wt%, after adjusting the pH to neutral, heating at 60°C for 30min; column chromatography uses DEAE-52 cellulose column, and gradient elution is performed with NaCl solution. Subsequent Examples 3 and 4 are prepared by the above method.
[0119] Exploration of process conditions for polysaccharide extraction and separation:
[0120] 1.1 Preparation of glucose standard curve
[0121] Accurately weigh an appropriate amount of glucose standard and dilute it to a 100 mL volumetric flask to obtain a glucose standard solution with a mass concentration of 7.9 mg / mL. Accurately pipette 0 mL, 0.20 mL, 0.40 mL, 0.60 mL, 0.80 mL, and 1.00 mL of liquid into colorimetric tubes, respectively, and then fill each tube to 1 mL with pure water, shake well, add 1 mL of 5% phenol solution, and then quickly add 5 mL of concentrated sulfuric acid, heat in 60℃ hot water for 30 min, cool to room temperature, and measure the glucose absorbance at 490 nm ultraviolet detection wavelength. With concentration as the x-axis and absorbance as the y-axis, a glucose standard curve was drawn. Results: The regression equation of Hibiscus mutabilis leaf polysaccharide is y=12.422x+0.0873, r= 0.9999. The linear relationship is good in the range of 0.016-0.08 mg / mL.
[0122] 1.2. Screening of polysaccharide extraction methods
[0123] 1.2.1 Hot water extraction method: Weigh 1 g of Hibiscus mutabilis leaf powder, add 50 mL of purified water, and perform heating reflux extraction for 2 h. Transfer the extract to a centrifuge tube, shake it thoroughly, and separate it by centrifugation for 10 min. Take the supernatant to obtain the polysaccharide solution.
[0124] 1.2.2 Pectinase extraction method: Weigh 1 g of Hibiscus mume leaf powder, add 50 mL of 0.1% pectinase water, weigh, extract for 2 hours, place at 90℃ for 4 minutes to terminate the reaction, add water to make up the weight. After shaking, centrifuge the solution for 10 minutes, and take the supernatant to obtain the polysaccharide solution.
[0125] 1.2.3 Cellulase extraction method: Weigh 1 g of Hibiscus mutabilis leaf powder, add 50 mL of 0.1% cellulase water, weigh, extract for 2 h, place at 90°C for 4 min to terminate the reaction, add water to make up the weight. After shaking, centrifuge the solution for 10 min, and take the supernatant to obtain the polysaccharide solution.
[0126] 1.2.4 Papain extraction method: Weigh 1 g of Hibiscus mutabilis leaf powder, add 50 mL of 0.1% papain water, weigh, extract for 2 h, place at 90°C for 4 min to terminate the reaction, add water to make up the weight. After shaking well, centrifuge the solution for 10 min, and take the supernatant to obtain the polysaccharide solution.
[0127] Results: The polysaccharide content under the action of cellulase was 40 mg / g, and the polysaccharide content obtained under the action of papain was 43 mg / g. The hot soaking method had the lowest content. Considering that papain can be used for subsequent crude polysaccharide purification, the papain extraction method was selected.
[0128] 1.3 Single Factor Experiment
[0129] The following test solutions were prepared according to the papain method in 1.2.4, and the absorbance was determined according to the conditions in 1.1:
[0130] 1.3.1 Screening of enzymatic hydrolysis time
[0131] The test sample solutions with enzymatic hydrolysis time of 1, 2, 3, and 4 h were prepared. Results: The content of polysaccharides in Hibiscus mutabilis leaves showed a trend of increasing first and then decreasing with the extension of enzymatic hydrolysis time, and reached a peak at 2 h. It may be that with the increase of enzymatic hydrolysis time, the tissue structure of the substrate was fully decomposed by the enzyme, which promoted the release of polysaccharides. With the further extension of enzymatic hydrolysis time, the optimal temperature of the enzyme may decrease, resulting in a decrease in enzyme activity and a gradual decrease in the content of polysaccharides. Therefore, this experiment selected enzymatic hydrolysis time of 1 h, 2 h, and 3 h as the three levels of the response surface.
[0132] 1.3.2 Screening of enzymatic hydrolysis temperature
[0133] The test sample solutions with enzymatic hydrolysis temperatures of 30, 40, 50, 60, 70, and 80°C were prepared. Results: The content of polysaccharides in Hibiscus mutabilis leaves showed a trend of increasing first and then decreasing with the increase of enzymatic hydrolysis temperature, and reached a peak at 50°C. On the one hand, the increase in temperature promoted the dissolution rate of polysaccharides in the solution, thereby improving the extraction efficiency; on the other hand, too high a temperature may damage the spatial configuration of the enzyme protein and reduce the enzyme activity, thereby reducing the amount of polysaccharide extraction. Therefore, this study decided to select enzymatic hydrolysis temperatures of 40°C, 50°C, and 60°C as three different levels in the response surface analysis.
[0134] 1.3.3 Screening of enzyme dosage
[0135] The test sample solutions with enzyme dosages of 0.5, 0.8, 0.9, 1.0, 1.1, 1.2, and 1.3% were prepared. Results: The polysaccharide content of Hibiscus mutabilis leaves showed a trend of first increasing and then decreasing with the increase of enzyme concentration. Under the condition of fixed substrate molecular weight, the enzymatic reaction rate was positively correlated with the enzyme concentration. The increase of enzyme concentration accelerated the decomposition of the substrate, thereby increasing the amount of polysaccharide extraction. When the enzyme concentration reached 1.3%, the enzyme water showed a slight suspension state, indicating that the enzyme water had reached saturation, and further increasing the enzyme concentration may lead to unstable data. Considering the extraction efficiency and production cost, this experiment selected 1.1%, 1.2%, and 1.3% as the three enzyme concentration levels for response surface analysis.
[0136] 1.3.4 Screening of material-liquid ratio
[0137] The test solutions were prepared with a solid-liquid ratio of 1:30, 1:40, 1:50, 1:60, and 1:70 mL / g, respectively. Results: The content of Hibiscus mutabilis leaf polysaccharide showed an overall trend of first increasing and then decreasing with the increase of liquid-to-solid ratio, and reached the highest at 60:1 (mL / g). Therefore, this experiment selected liquid-to-solid ratios of 50:1, 60:1, and 70:1 as the three levels of the response surface.
[0138] 6.2.5 Optimizing the process
[0139] According to the results of the single factor experiment, the extraction process of polysaccharides from Hibiscus mutabilis leaves was optimized using Design Expert 10.0.1 software. The factors and levels of response surface analysis are shown in Table 7;
[0140] Table 7 Analysis factors
[0141]
[0142] The software was used to analyze and fit the experimental data in Table 7, and the regression equation was obtained: Y=488.18+49.25A+26.74B+98.99C+7.53D-27.16AB+46.21AC+13.12AD+4.59BC-39.85BD-27.82CD-61.52A 2 -77.37B 2 -64.62C 2 -99.79D 2 . As shown in Table 1-16, P=0.0005 < 0.05, the model is significant. The lack of fit item P=0.148>0.05, the lack of fit test result is not significant, and the lack of fit test result shows that the model does not respond significantly to the unknown factors, so it can be inferred that the unknown factors have little effect on the model. Based on this, the model has a high degree of credibility in predicting and analyzing the polysaccharide extraction process and its comprehensive score. By comparing the F values within the range of each factor, the relative strength of the influence of the four main factors on the model can be determined, from strong to weak: enzymatic hydrolysis time (C), enzyme concentration (A), enzymatic hydrolysis temperature (B), and solid-liquid ratio (D). The three-dimensional response surface diagram was obtained using Design-Expert 12 software. According to the response surface fitting results, the optimal polysaccharide extraction process parameters were obtained as follows: enzyme concentration 1.23%, enzymatic hydrolysis time 2.45 h, enzymatic hydrolysis temperature 50.62℃, and solid-liquid ratio 1:57.54 g / mL. Taking into account the actual operating conditions, the enzymatic hydrolysis temperature was adjusted to 50 °C, the solid-liquid ratio was adjusted to 1:58 g / mL, the enzymatic hydrolysis time was 2.45 h, the enzyme concentration was 1.23%, and the average polysaccharide content of three parallel experiments was 532.26 mg / g, which was close to the predicted value of 531.85 mg / g, indicating that the process conditions were stable and feasible.
[0143] Embodiment 3:
[0144] As a preferred embodiment, a hibiscus leaf hydrogel is prepared by mixing 4 wt % sodium alginate aqueous solution, 2 wt % hibiscus leaf polysaccharide aqueous solution prepared in Example 2, and 4 wt % hibiscus leaf flavonoids prepared in Example 1 in a volume ratio of 1:1:1, pouring into a mold, and spraying with a cross-linking agent CaCl2 with a concentration of 2 wt %, to obtain the hibiscus leaf hydrogel. The subsequent Example 4 is a hydrogel prepared under the above conditions.
[0145] Exploration of preparation process conditions: (The percentage concentrations below are all mass percentage concentrations unless otherwise specified)
[0146] 3.1 Screening of matrix concentration
[0147] The Hibiscus mutabilis leaf polysaccharide prepared in Example 2 and the Hibiscus mutabilis leaf flavonoid powder prepared in Example 1 were weighed and prepared into a polysaccharide solution with a concentration of 2wt% and a flavonoid aqueous solution with a concentration of 4wt%, respectively. In addition, SA solutions of different concentrations (2%, 3%, 4%, 6%, 8%) and a calcium chloride solution with a concentration of 2% were prepared for standby use. The SA solution of equal volume ratio was mixed with a mixed solution containing Hibiscus mutabilis components (i.e., polysaccharide and flavonoid solution) and then poured into a mold, and a hydrogel structure was formed by spraying a CaCl2 solution. A total of 5 groups of samples (n=3 in each group) were prepared, and the moldability of these samples was observed and the swelling and degradability were measured.
[0148] 3.1.1 Formability
[0149] Results: The cross-linking degree of the hydrogel increased significantly with the increase of SA concentration. When the SA concentration reached 6%, the cross-linking degree of the hydrogel reached a dense state, resulting in incompleteness of its internal structure, which was manifested as increased brittleness and rough surface.
[0150] 3.1.2 Swelling degree
[0151] Studying the swelling degree of hydrogel in PBS can be used to evaluate the ability of hydrogel to absorb wound exudate when applied to wound dressings. The Hibiscus mutabilis leaf hydrogel samples were freeze-dried to a constant weight, and then weighed and the relevant data were recorded. The samples were placed in a PBS solution with a pH value of 7.4 and swelled at 37°C for 24 hours. After the hydrogel reached swelling equilibrium, the gel sample was carefully removed, and the PBS solution remaining on the surface of the gel was absorbed with filter paper, and then weighed again and the data was recorded. All samples will be repeated three times for in vitro swelling experiments. The calculation formula for in vitro swelling degree is as follows:
[0152] Swelling degree % = [(m 24 -m0) / m0]×100% (2-1)
[0153] m0 is the initial mass of the hydrogel; m 24 is the mass of the hydrogel after 24 hours in the swelling medium. Results: The 4% SA sample had the highest swelling degree, reaching 2667%±189.50%, while the 2% SA sample had the lowest swelling degree, 1630%±192.55%. This indicates that when the SA concentration is low, its swelling performance is poor due to insufficient cross-linking.
[0154] 3.1.3 Degradation rate
[0155] Hibiscus mutabilis leaf hydrogel samples were prepared, weighed and placed in test tubes, and 5 mL of phosphate buffer solution (PBS) with a pH value of 7.4 was added. The degradation experiment was carried out at 37°C and 100 rpm / min. The gel samples were taken out every 5 days, and the surface solution was removed with filter paper and weighed. The measurement was continued for 20 days. The in vitro degradation experiment was repeated 3 times for each sample.
[0156] Degradation rate%=[(m t -m0) / m0]×100% (2-2)
[0157] Note: m0 is the initial mass of the hydrogel, g; m t is the mass of the hydrogel at time t. Results The effect of different concentrations of SA on the in vitro degradation rate of the hydrogel was not significant. In the 30-day degradation experiment, the in vitro degradation rates of the five groups of hydrogels were 96.13%±1.66%, 96.57%±0.20%, 95.71%±0.42%, 93.87%±1.44%, and 91.80%±1.58%, respectively. The results showed that with the increase of the degree of cross-linking, the in vitro degradation rate of the hydrogel showed an overall downward trend.
[0158] 3.2 Screening of polysaccharide concentration
[0159] Prepare polysaccharide aqueous solutions prepared in Example 2 with mass concentrations of 0%, 2%, 4%, 6%, 8% and 10% and flavonoid solutions prepared in Example 1 with a mass concentration of 4%; prepare 4wt% SA aqueous solutions at the same time; then mix the above solutions evenly in a volume ratio of 1:1:1 and pour them into a mold, and form a gel structure by spraying 2wt% calcium chloride aqueous solution. Six groups of samples (n=3) were prepared in this study, and the swelling performance of each group of samples was tested. At the same time, they were comprehensively characterized by scanning electron microscopy, Fourier transform infrared spectroscopy analysis, and rheological property evaluation.
[0160] 3.2.1 Swelling degree
[0161] The test method was the same as 3.1.2. Results: The swelling degrees of the Hibiscus leaf polysaccharide groups with concentrations of 0%, 2%, 4%, 6%, 8% and 10% were 1980%, 2710%, 2250%, 2190%, 2150% and 2130%, respectively, that is, with the increase of the concentration of Hibiscus leaf polysaccharide, the swelling rate of the hydrogel showed a decreasing trend. It may be due to the cross-linking effect between polysaccharide and hydrogel, which leads to a tighter molecular network structure, thereby limiting the penetration of water molecules and reducing the swelling degree. However, compared with the blank control sample without Hibiscus leaf polysaccharide (0%), the gel sample containing Hibiscus leaf polysaccharide showed a higher swelling degree. This result shows that the swelling properties of the hydrogel can be improved by combining an appropriate amount of Hibiscus leaf polysaccharide with SA.
[0162] 3.2.2 Microscopic morphology of hydrogel
[0163] After freeze-drying the Hibiscus mutabilis leaf hydrogel, the freeze-dried hydrogel sample was immersed in liquid nitrogen to obtain a fracture cross section. After gold spraying, the fracture surface of the hydrogel was observed using a scanning electron microscope. Figure 3 As shown, Figure 3 The AF groups were 0%, 2%, 4%, 6%, 8% and 10% of Hibiscus mutabilis leaf polysaccharide. Figure 3 It can be seen that the pore structure of sample B (containing 2% polysaccharide) does not change significantly compared with sample A (0% polysaccharide). As the polysaccharide concentration increases, the pore structure of the gel gradually expands and the pore density decreases, thereby enhancing the stability of the hydrogel. When the polysaccharide concentration reaches 8%, the pore structure gradually disappears and turns into a wrinkled shape. In summary, the polysaccharide concentration is considered to be below 6%.
[0164] 3.2.3 Fourier transform infrared spectroscopy
[0165] After freeze-drying of the Hibiscus mutabilis leaf hydrogel, 2 mg of freeze-dried hydrogel sample was taken, KBr was added to press the pellet, and the spectrum was collected in the range of 4000-400 cm-1 at a resolution of 4 cm-1 on FTIR and plotted using Origin2021.
[0166] 3.2.4 Rheological tests
[0167] The mechanical properties of the hydrogel samples were characterized by rheological methods. The temperature was 25℃, the vibration frequency was 1 Hz, and the measurement was carried out in oscillation mode for 5 minutes, and the relevant data were recorded. Results: The storage modulus (G') of the 2% polysaccharide group was the largest, reaching 8939-14700Pa; the storage modulus (G') of the 6% polysaccharide group was the smallest, ranging from 6259 to 9509Pa, that is, the storage modulus (G') of the hydrogel sample was between 9509 and 14700Pa, indicating that the addition of Hibiscus mutabilis leaf polysaccharide changed the mechanical strength of the hydrogel. The storage modulus (G') and loss modulus (G'') did not intersect, indicating that the hydrogel had good stability. Considering comprehensively, a 2wt% Hibiscus mutabilis leaf polysaccharide solution was selected, at which the storage modulus and loss modulus were more appropriate.
[0168] 3.3 Screening of cross-linker concentration
[0169] The significant effect of calcium chloride concentration on the physical properties of SA. With the gradual increase of calcium chloride concentration, the tensile strength and water absorption rate of SA showed a trend of first increasing and then decreasing.
[0170] The inventors prepared 4% SA aqueous solution and 1%, 1.5%, 2%, 2.5% CaCl2 aqueous solution respectively, and carried out the crosslinker concentration screening test as described in 3.2 above. The results showed that when the crosslinker concentration was 2.0%, the swelling degree was optimal.
[0171] 3.4 Screening of volume ratio of matrix, Hibiscus mutabilis leaf polysaccharide and flavonoids
[0172] Weigh a certain amount of Hibiscus mutabilis leaf polysaccharide and flavonoid powder, and prepare 2% polysaccharide and 4% flavonoid aqueous solution respectively. Weigh a certain amount of SA and calcium chloride, and prepare 4% SA aqueous solution and 2% CaCl2 aqueous solution respectively for use. SA and aqueous solution containing Hibiscus mutabilis leaf polysaccharide and flavonoids were mixed into a mold in a volume ratio of 1:1:1, 2:1:1, 1:2:1, 1:1:2, and 2:2:1, and sprayed with CaCl2 to form a hydrogel. In this experiment, 5 groups (n=3) of samples were prepared, and the swelling degree was tested, supplemented by SEM, FTIR, and rheological tests. The results showed that the volume ratio of 1:1:1 had the best performance.
[0173] The above screening test proves that hydrogels prepared from a single material (SA) usually have disadvantages such as poor mechanical properties and low stability. Therefore, this application selects two natural polymer materials, SA and an appropriate amount of hibiscus leaf polysaccharide, to compositely prepare hibiscus leaf hydrogel, which can simultaneously ensure the mechanical properties and swelling properties of the hydrogel, and then adds hibiscus leaf flavonoids as the main active ingredient to exert synergistic anti-inflammatory, antioxidant and other effects.
[0174] Example 4
[0175] This example verifies the effect of the Hibiscus truncatula leaf hydrogel of the present invention on DU repair.
[0176] 4.1 Experimental Reagents
[0177] Streptozotocin (STZ): Sigma, S0130; paraformaldehyde: McLean, P885233; sodium chloride: Tianjin Aopusheng Chemical Co., Ltd., 20230401; sodium pentobarbital: Shanghai Fluoride Chemical Co., Ltd., M50179; TNF-α kit, IL-6 kit, IL-10 kit: Beijing Ruida Henghui Technology Development Co., Ltd.; medical recombinant type III humanized collagen repair gel: Newlian; anhydrous ethanol (AR): Chengdu Kelong Chemical Co., Ltd., 2023022401; normal saline: Sichuan Kelun Pharmaceutical Co., Ltd., N21040103A.
[0178] 4.2 Experimental animals
[0179] The experiment used 72 6-week-old SD rats from Chengdu Dashuo Experimental Animal Co., Ltd., weighing (200±20) g, and housed in the animal room on the fifth floor of the Pharmaceutical Experiment Center of Chengdu Medical College. The temperature was (24±2)℃ and the humidity was 40%-70%.
[0180] 4.3 Experimental methods
[0181] 4.3.1 Preparation of experimental drugs
[0182] About 300 mg of sodium pentobarbital was dissolved in 0.9 wt % sodium chloride solution and the volume was adjusted to 10 mL to prepare a sodium pentobarbital solution with a concentration of 0.3 wt %. Hibiscus mutabilis leaf hydrogel was prepared according to the method of Example 3, and the hibiscus mutabilis leaf flavonoids were replaced with an equal amount and concentration of hibiscus mutabilis leaf polysaccharide aqueous solution to prepare a blank hydrogel for later use.
[0183] 4.3.2 Establishment of DM rat model
[0184] SD male rats were fed a high-fat diet for 30 consecutive days, fasted for 14 h before induction, and injected with STZ (prepared with 0.1 mol / L citric acid buffer at pH 4.2 to 10 mg / mL, and the injection time was controlled within 15 minutes) at a dose of 40 mg / kg through the peritoneal cavity. Random blood glucose, body weight, and rat status were measured on days 3, 7, 14, and 21.
[0185] 4.3.3 Establishment of DU rat model
[0186] Modeling method: The rats were anesthetized with 30 mg / kg sodium pentobarbital, the hair on their backs was shaved, and the rats were disinfected with alcohol cotton pads. Two circular full-thickness skin wounds with a diameter of about 1.5 cm were made on the back using a puncher, reaching the fascia layer. After hemostasis, the wounds were naturally exposed.
[0187] The wounds were treated with Hibiscus mutabilis leaf hydrogel dressing and positive drug medical recombinant type III humanized collagen repair gel, and skin specimens were collected on days 3, 7, and 14 after injury. The rats were kept in single cages.
[0188] 4.3.4 Experimental groups and drug administration
[0189] The 72 male rats with successful modeling were randomly divided into 6 groups, namely blank group, model group, positive group, low concentration group (4 mg / ml), medium concentration group (8 mg / ml) and high concentration group (12 mg / ml), with 12 rats in each group. The dosing method of each group is as follows:
[0190] (1) Blank group: After disinfection with 75% alcohol, a blank hydrogel of Hibiscus mutabilis leaves (i.e., the Hibiscus mutabilis leaf flavonoids prepared in Example 1 were replaced with an aqueous solution of Hibiscus mutabilis leaf polysaccharides prepared in Example 2 of equal amount and concentration) was applied to the back ulcer and fixed with a medical pressure-sensitive adhesive, once a day for 14 days;
[0191] (2) Model group: no treatment after disinfection with 75% alcohol and fixed with medical pressure-sensitive adhesive;
[0192] (3) Positive group: After disinfection with 75% alcohol, apply medical recombinant type III humanized collagen repair gel to the back ulcer (just cover the ulcer) and fix it with medical pressure-sensitive adhesive, once a day for 14 days;
[0193] (4) Drug group: After disinfection with 75% alcohol, the Hibiscus mutabilis leaf hydrogel prepared in Example 3 was applied to the back ulcer and fixed with medical pressure-sensitive adhesive, once a day for 14 days.
[0194] 4.3.5 Index detection
[0195] 4.3.5.1 Observation of wound morphology
[0196] Wound healing time: There were 12 rats in each group. The wound healing was observed daily, and the wound being completely covered by epithelial tissue was used as the criterion for determining the healing time.
[0197] Wound healing rate: The ulcer wounds of rats were photographed 3, 7, and 14 days after local treatment. The unhealed wound area was measured using a computer image analysis system. The ulcer wound area was determined using ImageProPlus5.0 software, and the wound healing rate of rats after local treatment was calculated.
[0198] 4.3.5.2 ELISA method for determination of serum related factor index levels in rats
[0199] On the 14th day after treatment, three rats were randomly selected from each group, and 5 mL of blood was collected through the abdominal aorta to separate the serum. The levels of IL-10, IL-6, and TNF-α in the serum were detected by ELISA, and the operation was strictly in accordance with the instructions of the kit.
[0200] 4.3.5.3 Western blot (WB) method to detect the expression of related proteins in rat wound tissue
[0201] On the 14th day of the experiment, samples were collected from the skin wounds of rats in each group, and total protein was extracted by grinding and homogenization. Protein quantitative analysis was then performed. 50 μg of protein samples were selected for WB detection, and GAPDH was used as an internal reference. The expression levels of β-catenin, Rspo3 and GSK-3β proteins were quantitatively analyzed using Q550 image analysis software.
[0202] 4.4 Results 4.4.1 Results of DU rat model establishment The results of body weight are shown in Table 8. Rats showed symptoms of continuous drinking, overeating, irritability and excessive urination, and their body weight began to decrease after modeling. Random blood glucose was >16.7 mmol / L 3, 7 and 14 days after modeling, and the diabetic rat model was successfully established. On this basis, the backs of diabetic rats were punctured. The wound healing of rats was observed according to the method under 2.5.1.
[0205] Table 8 Body weight changes of random rats before and after modeling
[0206]
[0207] 4.4.2 Observation of wound morphology
[0208] The results are as follows Figure 4 As shown in Table 9, the wound healing rates are as follows: the wound healing rates of the blank group, positive group, low concentration group, medium concentration group and high concentration group were higher than those of the model group at 3, 7 and 21 days, and the wound healing rate of the blank group at 14 days was equivalent to that of the low concentration drug group, indicating that the Hibiscus mutabilis leaf polysaccharide prepared by the present invention also has the effect of promoting DU wound healing. The wound healing rate of the high concentration drug group reached 97.25% at 14 days, which was significantly higher than that of other groups, indicating that the Hibiscus mutabilis leaf hydrogel stimulated epithelial regeneration and promoted DU wound healing.
[0209] Table 9 Wound healing rates at 3, 7, and 14 days
[0210]
[0211] 4.4.3 Serum inflammatory factor levels
[0212] The levels of inflammatory factors in rat serum were determined, and the specific results are shown in Table 10. Compared with the blank group, the IL-6 concentration in the skin tissue of the model group was significantly increased (P <0.01). Further analysis showed that the IL-6 level in the positive control group, the medium-dose group, and the high-dose treatment group decreased relative to the model group (P <0.05), while no significant difference was observed between the low-dose groups (P >0.05). For IL-10, there was no statistically significant difference between the model group and the blank group (P >0.05), and the positive group and all dose gradient groups did not show significant changes compared with the model group (P >0.05). In addition, the expression of TNF-α in the model group was significantly increased compared with the blank group (P <0.01); the positive control group and the high-dose group showed lower TNF-α levels than the model group (P <0.01).
[0213] Table 10 Levels of inflammatory factors ( ±SD)
[0214]
[0215] Note: Compared with the blank group, the model group had *P<0.05, **P<0.01, ***P<0.001; Compared with the model group, # P<0.05, ## P<0.01, ### P<0.001.
[0216] In summary, the drug group had a significant inhibitory effect on TNF-α and IL-6 in rat serum, and a promoting effect on IL-10, which indicates that the hibiscus leaf hydrogel dressing prepared by the present invention mainly exerts its anti-inflammatory effect by reducing the expression of pro-inflammatory factors. At the same time, the blank group had a slight inhibitory effect on TNF-α and IL-6 in rat serum, and a promoting effect on IL-10, which indicates that hibiscus leaf polysaccharide may also have a certain anti-inflammatory effect with SA.
[0217] 4.4.4 Expression of related proteins in rat wound tissue
[0218] According to the method under 4.3.5.3, the expression of three proteins in the wound tissue of rats in the blank group, model group, positive group, low concentration group, medium concentration group, and high concentration group after 14 days of intervention is shown in Table 11. The expression levels of Rspo3 and β-catenin in the drug group and the positive group were significantly increased compared with those in the model group (P<0.001), and the expression level of GSK3β was significantly decreased (P<0.001), and the drug group was better than the positive group. This shows that the treatment of DU by Hibiscus mume leaf hydrogel may be related to the regulation of the Wnt / β-catenin pathway.
[0219] Table 11 Expression of related proteins
[0220]
[0221] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a flavonoid extract from Hibiscus mutabilis leaves, characterized in that: The steps include: (1) After the dried Hibiscus mutabilis leaves are crushed, ethanol with a volume percentage concentration of 60% to 90% is added, and the solid-liquid ratio is 1:10 g / ml to 1:40 g / ml, and ultrasonic extraction is performed to obtain a Hibiscus mutabilis leaf extract; (2) The hibiscus mutabilis leaf extract obtained in step (1) is separated and purified using a macroporous resin to obtain a hibiscus mutabilis leaf flavonoid extract.
2. The method according to claim 1, characterized in that In step (1), ultrasonic extraction is performed twice, each time for 10 min to 30 min; the volume percentage concentration of the ethanol is 60% to 80%; and the solid-liquid ratio is 1:10 g / mL to 1:30 g / mL.
3. The method according to claim 2, characterized in that The ultrasonic extraction lasted for 26 min each time, the volume percentage concentration of ethanol was 66%, and the solid-liquid ratio was 1:26 g / mL.
4. The method according to claim 1, characterized in that In step (2), AB-8 macroporous resin is used as the adsorption resin, the concentration of the loading solution is 1 to 3 g / mL, the loading flow rate is 1 to 3 mL / min, and the eluent is ethanol with a volume percentage concentration of 30% to 60%.
5. A method for preparing a polysaccharide extract from Hibiscus mutabilis leaves, characterized in that: The steps include: (1) Pretreatment: The Hibiscus mutabilis leaf powder was pretreated to remove pigments; (2) Extraction: The polysaccharide from Hibiscus mutabilis leaf was extracted by papain extraction method; (3) Purification: First, the TCA method is used to remove the protein, and then cellulose column chromatography is used to obtain Hibiscus mutabilis leaf polysaccharide.
6. The method according to claim 5, characterized in that In step (1), the pretreatment method is: Soxhlet extraction with 95 vol% ethanol for 2 h; In step (2), the enzyme concentration was 1.23%, the enzymatic hydrolysis time was 2.45 h, the enzymatic hydrolysis temperature was 50°C, and the solid-liquid ratio was 1:58 g / mL; In step (3), the concentration of trichloroacetic acid added during deproteinization is 5 wt %, and after adjusting the pH to neutral, heating is performed at 60° C. for 30 min. A DEAE-52 cellulose column is used for column chromatography, and a NaCl solution is used for gradient elution.
7. A Hibiscus mutabilis leaf hydrogel, characterized in that: The hibiscus leaf hydrogel is obtained by using the hibiscus leaf polysaccharide and sodium alginate prepared according to claim 4 or 5 as a composite matrix material, loading the hibiscus leaf flavonoids prepared according to any one of claims 1 to 3 as a medicinal ingredient, and cross-linking with a cross-linking agent.
8. The Hibiscus mutabilis leaf hydrogel according to claim 7, characterized in that The specific preparation method is as follows: 2wt% to 6wt% of sodium alginate, 2wt% to 6wt% of hibiscus leaf polysaccharide, and 2wt% to 6wt% of hibiscus leaf flavonoids are mixed in a volume ratio of (1-2):(1-4):(1-2), poured into a mold, and sprayed with a cross-linking agent CaCl2 with a concentration of 1wt% to 2.5wt% to obtain hibiscus leaf hydrogel.
9. The Hibiscus mutabilis leaf hydrogel according to claim 8, characterized in that The specific preparation method is: 4wt% sodium alginate, 2wt% hibiscus leaf polysaccharide and 4wt% hibiscus leaf flavonoids are mixed in a volume ratio of 1:1:1 and poured into a mold, and then sprayed with 2wt% cross-linking agent CaCl2 to obtain hibiscus leaf hydrogel.
10. Use of the hydrogel according to any one of claims 7 to 9 in the preparation of a medicament for treating diabetic ulcers.